Characterizing caregiver responses to restricted and repetitive behaviors in toddlers with autism spectrum disorder. (April 2016) - Harrop, Clare; Gulsrud, Amanda; Shih, Wendy; Hovsepyan, Lilit; Kasari, Connie
Restricted and repetitive behaviors are a core feature of autism spectrum disorder. This descriptive study documented the presence of restricted and repetitive behaviors in 85 toddlers with autism spectrum disorder as they interacted with their caregiver in a play interaction. For each child restricted and repetitive behavior, a caregiver response/non-response was coded. Caregiver responses were rated as successful or unsuccessful. In all, 83 toddlers demonstrated at least one restricted and repetitive behavior in 10 min. The most common child restricted and repetitive behavior was repetitive object use with 72 children displaying at least one instance of this category of restricted and repetitive behavior. Overall, caregivers responded to fewer than half of their child's restricted and repetitive behaviors, and caregiver response varied by child restricted and repetitive behavior type. The most common response was redirection. Success varied by child restricted and repetitive behavior type and caregiver response—redirections were most successful for child verbal and motor restricted and repetitive behaviors, whereas physical or verbal responses were rated more successful for repetitive object use and visual restricted and repetitive behaviors. This study represents the first attempt to characterize how caregivers respond to restricted and repetitive behaviors. Toddlers with autism spectrum disorder are already demonstrating a variety of restricted and repetitive behaviors within the context of a free play sessions, and caregivers differentially and naturally respond to them.